ANALISIS KETERAMPILAN TEKNIK BOWLING ATLET CRICKET KABUPATEN KERINCI UNTUK PERSIAPAN PORPROV JAMBI PADA TAHUN 2023 - Randi Prastio; Edo Yuliandra Pratama; Anggil Jufinda (EDU RESEARCH, 2023)
This study aims to make kerinci district cricket athletes understand more about bowling techniques in cricket games and improve bowling technique skills to achieve maximum results in bowling... This research was conducted at the old local government field in Sungai Penuh city. Data collection was carried out on 22 March - 02 April 2023. This research method is to use quantitative descriptive research and the technique used is a survey in the form of a percentage of success and failure in bowling. The population and sample of this study were all cricket athletes in Kerinci district totalling 22 people consisting of 11 men and 11 women in preparation for porprov jambi in 2023. Based on the problems raised and supported by the description of the theory and conceptual framework and then analyse the data, the results of the study can be concluded as follows: kerinci district cricket athletes for fast bowling and slow bowling technique skills have mastered well, while for swing bowling and spin bowling technique skills have not mastered well, but there are still weaknesses in bowling, namely the lack of power or strength when throwing. and the placement of balls that still do not hit the target. And the placement of the ball that still does not hit the target or stump, of course, by doing maximum coaching and training, of course, it can minimise errors when bowling.